Living through World War II - Eboch, M. M. (American culture & conflict., 2019)
Examines the effect WWII had on the lives of individuals living in the United States. Explores both the immediate and long-term effects of the conflict on the society and culture. Includes maps, archival photographs, a glossary, and resources for further information.